PENGARUH MOTIVASI BELAJAR, MINAT BELAJAR DAN PENERAPAN PEMBELAJARAN DARING TERHADAP HASIL BELAJAR PRODUKTIF JURUSAN TEKNIK KOMPUTER DAN JARINGAN DI SMK NEGERI 5 GOWA PADA MASA COVID-19 - Andi Rahmania Hair; Purnamawati; Hamsu Abdul Gani (UNM Journal of Technology and Vocational, 2022)
This study aims to discover the direct and indirect influence of productive learning outcomes of the Computer and Network Engineering Department at SMKN 5 Gowa during the covid-19 period. The type of research used is quantitative with a survey method. The population in this study was 260 people and the research samples were 96 people obtained by using a proportional random sampling technique. The research data were obtained using a questionnaire instrument in a google form which was distributed to students. The data analysis technique is descriptive analysis and path analysis using the IBM Amos 26.0 application. The results show that: (1) there is no direct and significant influence of learning motivation on online learning application, (2) there is a direct and significant positive influence of learning interest on online learning application, (3) there is no direct and significant influence on online learning application, (4) there is a direct and significant positive influence of learning motivation on the results, (5) there is a direct and significant positive influence of learning interest on productive learning outcomes, (6) there is no indirect and significant influence of learning motivation on learning outcomes through online learning application as an intervening, and (7) thereis no indirect and significant influence of learning interest on learning outcomes through online learning application as an intervening variable.